Analysis of Students' Mathematical Representation Ability Based on Mathematics Ability - karomah, ilo guruilo; Dwi Astiati, Siska (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this research is to explore and describe students' mathematical representation abilities based on their level of mathematical ability. This type of research is descriptive with a qualitative approach. The research subjects were 25 students, 13 male students and 12 female students. Then 3 students with high, medium and low abilities were selected. The research results show that highly skilled subjects can re-present information or data from certain representations in the form of visual representations, can express mathematical equations and write down steps to solve mathematical problems in words. Subjects with moderate abilities only present information or data from certain representations in the form of visual representations and express mathematical equations. while low ability subjects can only solve problems involving mathematical expressions or equations. Basically, mathematical representation skills are very important and needed by students to understand the material provided and solve problems. If mathematical representation skills are lacking, it causes a lack of student understanding of the material provided so that students find it difficult to understand and work on the questions provided.